2021
DOI: 10.1093/hmg/ddab154
|View full text |Cite
|
Sign up to set email alerts
|

Placental endocrine insufficiency programs anxiety, deficits in cognition and atypical social behaviour in offspring

Abstract: Abnormally elevated expression of the imprinted PHLDA2 gene has been reported in the placenta of human babies that are growth restricted in utero in several studies. We previously modelled this gene alteration in mice and found that just two-fold increased expression of Phlda2 resulted in placental endocrine insufficiency. In addition, elevated Phlda2 was found to drive fetal growth restriction (FGR) of transgenic offspring and impaired maternal care by their wild type mothers. Being born small and being expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 103 publications
0
8
0
1
Order By: Relevance
“…Our work on mice with placental endocrine insufficiency driven by genetically modified changes in the expression of imprinted genes further demonstrates a role for placental hormones in regulating birthweight with a reduction in the number of placental endocrine cells linked to low birthweight in several models (39-41). We also reported both maternal neglect and maternal anxiety in response to the loss of placental endocrine lineages (42, 43) with the mouse offspring exhibiting anxiety-like behaviours later in life (44). Together, these data highlight the importance of placental hormones, and more specifically placental lactogens, for pregnancy health.…”
Section: Introductionmentioning
confidence: 66%
“…Our work on mice with placental endocrine insufficiency driven by genetically modified changes in the expression of imprinted genes further demonstrates a role for placental hormones in regulating birthweight with a reduction in the number of placental endocrine cells linked to low birthweight in several models (39-41). We also reported both maternal neglect and maternal anxiety in response to the loss of placental endocrine lineages (42, 43) with the mouse offspring exhibiting anxiety-like behaviours later in life (44). Together, these data highlight the importance of placental hormones, and more specifically placental lactogens, for pregnancy health.…”
Section: Introductionmentioning
confidence: 66%
“…A 2-fold increase of expression of one of these imprinted genes, Phlda2 , in the mouse foetus leads to a 50% decrease in the size of the placental endocrine compartment; conversely, loss of Phlda2 expression results in a doubling in size of the endocrine compartment [ 87 ]. Both these manipulations of Phlda2 expression in the foetal placenta have consequences for gene expression in the maternal brain and parental care behaviour in the early postnatal phase [ 88 ]; this in turn can have knock-on consequences for offspring brain and behaviour later in life [ 89 ].…”
Section: Indirect Action Of Imprinted Genes On Brain and Behaviourmentioning
confidence: 99%
“…We have demonstrated that placental endocrine insufficiency can cause low birth weight (Salas et al., 2004; Tunster et al., 2010, 2014; Tunster, McNamara, et al., 2016) and alterations in the behaviour of the mother (Creeth et al., 2018; McNamara et al., 2018) and her offspring (Harrison et al., 2021) in mice (Figure 1a). These studies in experimental animal models identify an alternative mechanism whereby adversity‐driven placental endocrine insufficiency causes both the mood disorder in the mother and the poor health outcome for the child.…”
Section: Relevance To Human Pregnancymentioning
confidence: 99%
“…In order to distinguish between the direct effect of genetically elevated Phlda2 and the indirect effect of an adverse environment, we generated litters in which half the pups carried the Phlda2 transgene (low birth weight plus adverse environment; transgenic) and half were genetically wild‐type but raised in the same adverse environment (which we refer to as non‐transgenic). These offspring were studied concurrently alongside fully wild‐type litters raised by wild‐type dams as environmental controls (Harrison et al., 2021 ). Both male and female offspring were put through a battery of behavioural tests to probe anxiety‐associated behaviours, depression‐like behaviours, aspects of learning and attention, and social behaviours.…”
Section: Placental Endocrine Insufficiency and Later Life Behaviourmentioning
confidence: 99%